Wake respirometry allows breath-by-breath assessment of ventilation and CO2 production in unrestrained animals - Kayleigh Rose (iScience, 2022)
Quantifying stress and energetic responses in animals are major challenges, as existing methods lack temporal resolution and elevate animal stress. We propose‘‘wake respirometry,’’ a new method of quantifying fine-scale changes in CO2 production in unrestrained animals, using a nondispersive infrared CO2 sensor positioned downwind of the animal, i.e., in its wake. We parameterize the dispersionof CO2 in wakes using known CO2 flow rates and wind speeds. Tests with threebird species in a wind tunnel demonstrated that the system can resolve breathby-breath changes in CO2 concentration, with clear exhalation signaturesincreasing in period and integral with body size. Changes in physiological statewere detectable following handling, flight, and exposure to a perceived threat.We discuss the potential of wake respirometry to quantify stress and respiratorypatterns in wild animals and provide suggestions for estimating behavior-specificmetabolic rates via full integration of CO2 production across the wake.